The impact of information and communication technology and internal market orientation blending on organisational performance in small and medium enterprises - Sergey Kazakov; José L. Ruiz-Alba; María M. Mu\~noz (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The present study examines the concept of internal market orientation (IMO) and its effects on organisational performance comprising job satisfaction and employees' loyalty in the small and medium enterprises (SMEs) research context. Rooted in administrative theory, human relations theory, conventional theories of IMO and internal marketing, this study develops a novel iIMO theoretical framework that evinces the proliferation of ICTs in SMEs. Design/methodology/approach - The proposed concept was empirically investigated by means of surveying 316 SME employees with the application of a multi-stage sampling procedure. Findings - Research findings confirmed the viability of the ICT-supported iIMO framework, its positive effects on SMEs' organisational performance, and exhibited ample empirical evidence for the proficiency of the iIMO concept and its suitability for operationalisation by SMEs. Originality/value - This study introduces ICTs as a novel IMO dimension which considers the undergoing holistic digitalisation of businesses. In addition, the present research posits the plausibility and confirms the benefits that arise following iIMO implementation in SMEs.
Keywords: 650; Internal market orientation; Internal marketing; Job satisfaction; Market orientation; Organisational performance; SMEs